BOLBITIS NAGALANDENSE R. R. RAO & N. S. JAMIR A NEW SPECIES OF LOMARIOPSIDACEAE FROM NAGALAND, INDIA - R. R. Rao; N. S. JAMIR (Research Center for Biology, 1984)
An illustrated description of the new species Bo-lbitis nagalandense is presented